Spontaneous separation in idiopathic vitreomacular traction syndrome associated with contralateral full-thickness macular hole (2006)
PURPOSE. Vitreomacular traction syndrome (VMTS) and full-thickness macular hole are two different well-known entities that on follow-up may be subjected to clinical modifications. Precisely, a spontaneous separation of idiopathic VMTS occurred in three eyes of three patients relieving in addition traction of the posterior hyaloid that had led also to a focal macular retinal pigment epithelial detachment (RPE). An association to a full-thickness macular hole was observed in the contralateral eye of one of the patients. METHODS. This is a retrospective study of three patients evaluated with fluorescein angiography and documented with optical coherence tomography using the Stratus (OCT) model 3000, with scans analysis and protocols analysis, measuring the size and shape of vitreomacular adhesions, macular thickness changes before and after the spontaneous separation of the tractional posterior hyaloid adhesion. In addition, the vitreous was evaluated with contact lens slit lamp biomicroscopy and ultrasound. The associated contralateral macular hole in one of the patients was surgically treated. RESULTS. Two of the three eyes with spontaneous separation of the VMTS recovered 20/25 central visual acuity; the other eye maintained the initial 20/50 visual acuity. The treated macular hole recovered 20/100 corrected visual acuity. CONCLUSIONS. Spontaneous separation of posterior hyaloid is a possible outcome during follow-up of idiopathic VMTS that can be well evaluated and documented with OCT while macular fluorescein angiography may be silent in cases like these presently reported. Central vision recovery can be excellent following the spontaneous separation, which releases anterior-posterior traction including on the retinal pigment epithelium and decreases macular thickness as measured with OCT. Therefore, regarding management, the indication for vitrectomy should be delayed awaiting the spontaneous release of vitreomacular traction in 4 to 6 months. The association between idiopathic VMTS in one eye and full-thickness macular hole in the opposite eye of one patient is an important pathophysiologic consideration. © Wichtig Editore, 2006.